(x-0.3)+(2x-0.2)+((40+x)-0.25)=274

Simple and best practice solution for (x-0.3)+(2x-0.2)+((40+x)-0.25)=274 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (x-0.3)+(2x-0.2)+((40+x)-0.25)=274 equation:


Simplifying
(x + -0.3) + (2x + -0.2) + ((40 + x) + -0.25) = 274

Reorder the terms:
(-0.3 + x) + (2x + -0.2) + ((40 + x) + -0.25) = 274

Remove parenthesis around (-0.3 + x)
-0.3 + x + (2x + -0.2) + ((40 + x) + -0.25) = 274

Reorder the terms:
-0.3 + x + (-0.2 + 2x) + ((40 + x) + -0.25) = 274

Remove parenthesis around (-0.2 + 2x)
-0.3 + x + -0.2 + 2x + ((40 + x) + -0.25) = 274

Remove parenthesis around (40 + x)
-0.3 + x + -0.2 + 2x + (40 + x + -0.25) = 274

Reorder the terms:
-0.3 + x + -0.2 + 2x + (40 + -0.25 + x) = 274

Combine like terms: 40 + -0.25 = 39.75
-0.3 + x + -0.2 + 2x + (39.75 + x) = 274

Remove parenthesis around (39.75 + x)
-0.3 + x + -0.2 + 2x + 39.75 + x = 274

Reorder the terms:
-0.3 + -0.2 + 39.75 + x + 2x + x = 274

Combine like terms: -0.3 + -0.2 = -0.5
-0.5 + 39.75 + x + 2x + x = 274

Combine like terms: -0.5 + 39.75 = 39.25
39.25 + x + 2x + x = 274

Combine like terms: x + 2x = 3x
39.25 + 3x + x = 274

Combine like terms: 3x + x = 4x
39.25 + 4x = 274

Solving
39.25 + 4x = 274

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-39.25' to each side of the equation.
39.25 + -39.25 + 4x = 274 + -39.25

Combine like terms: 39.25 + -39.25 = 0.00
0.00 + 4x = 274 + -39.25
4x = 274 + -39.25

Combine like terms: 274 + -39.25 = 234.75
4x = 234.75

Divide each side by '4'.
x = 58.6875

Simplifying
x = 58.6875

See similar equations:

| -10(X+1)=8 | | -6x+15=-33 | | 3x-5(x-4)=-8+3x+3 | | 4x-8=4x+-5 | | 45+4x+7+57x=8 | | 2c-4=c+2 | | 4(3x-2)+4(x+1)=100 | | 7a+2a=18-9 | | 2=-3c+26 | | 3x+8x+4=12x+2 | | 8a+10=82 | | 2x+3-2(x-2)=-3(x+1)+22 | | 8n^2+8n=160 | | 3(X+20)=360 | | 0.92=0.4+0.1 | | 19+(-34)=2.8e+12 | | 8(2x+3)-(11x-4)=3 | | 10(3x-5)=40 | | 2-x=-3(x+4)+6 | | 8(16x+3)-(11x+4)=3 | | 5x-3-2x=12 | | 3(4s+1)=99 | | 2kx+x=2a+b | | 6x-4+3x+1=24 | | b+2b+1= | | 6(2y+5)=3(5y-2) | | 2X-100=22 | | 2(x+3)3(x+1)=24 | | 8(2l+9)=248 | | 5x^2-4x-64.01=0 | | 4x+6x=12x | | -2.66n+21=-0.33n |

Equations solver categories